Fibrosis, gene expression and orbital inflammatory disease. Issue 10 (2nd June 2015) - Rosenbaum, James T; Choi, Dongseok; Wilson, David J; Grossniklaus, Hans E; Harrington, Christina A; Dailey, Roger A; Ng, John D; Steele, Eric A; Czyz, Craig N; Foster, Jill A; Tse, David; Alabiad, Chris; et al.
Abstract : Background/aims: To clarify the pathogenesis of fibrosis in inflammatory orbital diseases, we analysed the gene expression in orbital biopsies and compared our results with those reported for idiopathic pulmonary fibrosis. Methods: We collected 140 biopsies from 138 patients (58 lacrimal glands; 82 orbital fat). Diagnoses included healthy controls (n=27), non-specific orbital inflammation (NSOI) (n=61), thyroid eye disease (TED) (n=29), sarcoidosis (n=14) and granulomatosis with polyangiitis (GPA) (n=7). Fibrosis was scored on a 0–3 scale by two experts, ophthalmic pathologists. Gene expression was quantified using Affymetrix U133 plus 2.0 microarray. Results: Within orbital fat, fibrosis was greatest among subjects with GPA (2.75±0.46) and significantly increased in tissue from subjects with GPA, NSOI or sarcoidosis (p<0.01), but not for TED, compared with healthy controls (1.13±0.69). For lacrimal gland, the average score among controls (1.36±0.48) did not differ statistically from any of the four disease groups. Seventy-three probe sets identified transcripts correlating with fibrosis in orbital fat (false discovery rate <0.05) after accounting for batch effects, disease type, age and sex. Transcripts with increased expression included fibronectin, lumican, thrombospondin and collagen types I and VIII, each of which has been reported upregulated in pulmonary fibrosis. Conclusions: A pathologist's recognition of fibrosis in orbital tissue correlates well with increased expression of transcripts that are considered essential in fibrosis. Many transcripts implicated in orbital fibrosis have been previously implicated in pulmonary fibrosis. TED differs from other causes of orbital fat inflammation because fibrosis is not a major component. Marked fibrosis is less common in the lacrimal gland compared with orbital adipose tissue.